Decarcerating America : Once Again - Ernest Drucker (Social Medicine Publication Group, 2018)
The original meaning of Decarceration first hit me in 1964, when I was a clinical psychology intern in Brooklyn, at the Maimonides Hospital Department of Psychiatry where I first saw youthful drug users as patients, and ( more often ) in the streets of the community. This was before the "war on drugs" was declared by Pres. Nixon in a press conference on June 17, 1971, at which time President Nixon declared drug abuse "public enemy number one." But at this point in history even socially oriented institutions like Maimonides had little clinical experience with drug users - and the American criminal justice system had yet to discover and imprison them.